Cutaneous sarcoidosis as upsurging mimicking granulomatous diseases - Sharquie, Khalifa; Kubaisi, Thamir A; Sharquie, Inas K (Journal of Pakistan Association of Dermatologists, 2024)
Background Cutaneous manifestations of sarcoidosis are seen in around 25% of patients with sarcoidosis and that usually accompanies systemic involvement. Non-caseating granuloma is the classical histopathological picture. Sarcoidosis shares many clinical and histopathological features with many granulomatous diseases. Â Objective To do full clinical and histopathological evaluation of all cases that were diagnosed with cutaneous sarcoidosis, trying to find clinical limitations and borders between sarcoidosis and other granulomatous mimicking diseases. Â Methods This is a descriptive study where all patients that were diagnosed with cutaneous sarcoidosis during the period from 2014-2023 were assessed regarding dermographic features, clinical pictures and histopathological examination. An appropriate general physical examination as well as investigative techniques were implemented to detect the presence or absence of systemic involvements. Â Results This study included 24 patients, whose ages ranged from 27-70 years with a mean of 47.8 years with 16 (66.7%) females and 8 (33.3%) males. All patients had shiny smooth, skin colored or dusky red papules, nodules or plaques but rarely scaly. No obvious systemic involvements were detected by physical examination or investigative techniques. The histopathological assessment showed marked granulomatous reaction consisting of multiple non-caseating non-necrotizing granuloma formations. Â Conclusion Sarcoidosis is emerging as not a rare cutaneous disease that can mimic and compete with other granulomatous diseases. There is no specific available test for this disease but identifying the full cutaneous and pathological features is mandatory and might lead us to the correct diagnosis, hence it is an exclusion disease. Â